2018
DOI: 10.1016/j.atherosclerosis.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial respiration in human carotid plaque atherosclerosis: A potential role for Pink1 in vascular smooth muscle cell energetics

Abstract: We have identified a subset of plaque VSMCs required for plaque stability that have increased mitochondrial dysfunction and decreased oxidative phosphorylation. Pink1 kinase may initiate a cellular response to promote a compensatory glycolytic program associated with upregulation of AMPK and Hex2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
1
36
0
1
Order By: Relevance
“…Although reduced G6PD expression may be due to the inhibition of glucose-6-phosphate, and the down-regulation of IDH expression may be attributed to mitochondrial dysfunction caused by PDK4 activation 13 , all these findings suggest that AGEs inhibit glycolysis and impair normal mitochondrial function during VSMC calcification. A recent report has suggested that during atherogenesis, VSMCs have increased mitochondrial dysfunction and use of glycolysis; enhanced glycolysis could be a compensatory response to energetic failure 50 . In our study, AGEs induced mitochondrial dysfunction during VSMC calcification as measured by the expression of key enzymes of Kreb’s cycle and by OCR.…”
Section: Discussionmentioning
confidence: 99%
“…Although reduced G6PD expression may be due to the inhibition of glucose-6-phosphate, and the down-regulation of IDH expression may be attributed to mitochondrial dysfunction caused by PDK4 activation 13 , all these findings suggest that AGEs inhibit glycolysis and impair normal mitochondrial function during VSMC calcification. A recent report has suggested that during atherogenesis, VSMCs have increased mitochondrial dysfunction and use of glycolysis; enhanced glycolysis could be a compensatory response to energetic failure 50 . In our study, AGEs induced mitochondrial dysfunction during VSMC calcification as measured by the expression of key enzymes of Kreb’s cycle and by OCR.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, there is no debate concerning the presence of metabolic and mitochondrial dysfunction. This mitochondrial dysfunction has a significant impact on many cells within the body and could potentially be responsible for VSMC loss that is so pronounced in progeria [110,111]. Further, previous research has shown that HGPS patients are resistant to cancer due to the actions of BRD4, which inhibits tumorigenic potential of transformed cells [112].…”
Section: A Case For Metabolismmentioning
confidence: 99%
“…After the addition of mitophagy inhibitors, mitophagy and its related pathway proteins are significantly decreased, and cell apoptosis is significantly increased [145]. Mitophagy protects against atherosclerotic stress-induced apoptosis in human vascular smooth muscle cells (VSMCs) [146][147][148]. PINK1/Parkin was reportedly upregulated in atherosclerotic disease models than in normal tissues.…”
Section: Atherosclerosismentioning
confidence: 99%
“…PINK1/Parkin was reportedly upregulated in atherosclerotic disease models than in normal tissues. PINK1 overexpression enhances the protective effect of mitophagy on VSMCs, whereas PINK1 gene knockout counteracts it [146,147]. Hence, mitophagy is a potential target for the stabilization of atherosclerotic plaques.…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation